Korean Unification and Banking System - An Analysis in View of German Experiences and Korean Differences - Ralf Müller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2001)
One of the reforms that have to be launched in a future unification process in Korea, which seems possible after the political negotiations last year, is the transformation of the North Korean banking system. The question arises whether Korea could profit from the German experience where banking transformation was one of the rather few success stories in unification. In 1990 the East German banking transformation was achieved relatively fast and uncomplicated due to considerable direct investments of the West German banks compounded with state guarantees for bad loans resulting from the credit business with existing GDR-corporations. Unfortunately, South Korea currently lacks some major prerequesites that contributed to the German banking unification, among them - and probably the most important one - is the lack of a sound and efficient banking system that could become active in the North. Consequently, depending on the circumstances of a future Korean unification either a more gradual process is recommended or, if inner-Korean migration requires a more dynamic transition, considerable investment by foreign banks and assistance from international organisations is recommended.
urn:nbn:de:gbv:3:2-19110
Keywords: G21; N25; P21; 330; banking; East Germany; Korea; transformation; unification; Finanzsystem; Systemtransformation; Nationale Einheit; Korea; Deutschland